Acquisition, Synthesis, and Rendering of Bidirectional Texture Functions - Müller, G.; Meseth, J.; Sattler, M.; Sarlette, R.; Klein, R. (Computer graphics forum, 2005)
One of the main challenges in computer graphics is still the realistic rendering of complex materials such as fabric or skin. The difficulty arises from the complex meso structure and reflectance behavior defining the unique look‐and‐feel of a material. A wide class of such realistic materials can be described as 2D‐texture under varying light‐ and view direction, namely, the Bidirectional Texture Function (BTF). Since an easy and general method for modeling BTFs is not available, current research concentrates on image‐based methods, which rely on measured BTFs (acquired real‐world data) in combination with appropriate synthesis methods. Recent results have shown that this approach greatly improves the visual quality of rendered surfaces and therefore the quality of applications such as virtual prototyping. This state‐of‐the‐art report (STAR) will present the techniques for the main tasks involved in producing photo‐realistic renderings using measured BTFs in details.